P-BN63 Requirement of preoperative group and save testing prior to cholecystectomy: A systematic review. (16th December 2021) - Fadel, Michael; Patel, Ishaan; O'Leary, Lawrence; Behar, Nebil; Brewer, James
Abstract: Background: Group and save (G&S) testing is usually performed prior to cholecystectomy. However, there are no standard national or international guidelines regarding the routine use of preoperative G&S testing for patients undergoing emergency laparoscopy. Methods: We evaluated the available literature on the necessity of G&S prior to cholecystectomy to determine whether this was required preoperatively. Studies from January 1980 to May 2021 assessing the requirement of G&S were retrieved from MEDLINE and EMBASE databases. Number of patients, co-morbidities, operation performed, number of patients that underwent preoperative G&S testing, perioperative transfusion rates and financial costs were extracted. Results: We initially screened 194 studies of which 11 retrospective studies reported on cholecystectomy. A total of 177, 692/474, 485 (37.4%) patients underwent preoperative G&S testing with a perioperative transfusion rate of 2.07% (9803/474, 485 patients, range 0.0% to 1.6%). The main preoperative risk factors, where recorded, associated with perioperative blood transfusion identified include cardiovascular co-morbidity (16/45, 35%), coagulopathy (13/45 patients, 28%), anaemia (9/45 patients, 20%) and haematological malignancy (6/45, 13%). All 11 studies concluded that routine G&S is not warranted. Conclusions: The current evidence, though limited, suggests that G&S is not necessarily required for all patients undergoing cholecystectomy. Preoperative testing should be performed in selected cases, for example in septic coagulopathy, anaemia and haematological malignancy. There is no evidence to suggest that routine G&S screening benefits patient outcomes. Having a targeted G&S approach would reduce delays in elective and emergency lists, reduce the burden on the blood transfusion service and have financial implications.